The MAPS model of self-regulation: Integrating metacognition, agency, and possible selves - Frazier, Leslie D. (Metacogn Learn, 2021)
Self-regulation, a social-cognitive process at the intersection of metacognition, motivation, and behavior, encompasses how people conceptualize, strive for, and accomplish their goals. Self-regulation is critical for behavioral change regardless of the context. Research indicates that self-regulation is learned. Integral to successful self-regulation of behavior are: (a) an articulated concept of one’s possible selves, (b) metacognitive knowledge and effective strategies, and (c) a sense of one’s own agency. We present the theoretical linkages, research evidence, and applied utility for these three components in promoting self-regulation of behavior, specifically in the domain of learning. We propose the MAPS model to account for the pathways of influence that lead to behavioral change. This model illustrates the dynamic and feed-forward processes that derive from the interactions among possible selves, metacognition, and agency to provide the context for developing self-regulated and effective learning that promotes student success, the transfer of knowledge, and the foundation for life-long learning.